2019
DOI: 10.1371/journal.pbio.3000163
|View full text |Cite
|
Sign up to set email alerts
|

Brain expansion promoted by polycomb-mediated anterior enhancement of a neural stem cell proliferation program

Abstract: During central nervous system (CNS) development, genetic programs establish neural stem cells and drive both stem and daughter cell proliferation. However, the prominent anterior expansion of the CNS implies anterior–posterior (A–P) modulation of these programs. In Drosophila , a set of neural stem cell factors acts along the entire A–P axis to establish neural stem cells. Brain expansion results from enhanced stem and daughter cell proliferation, promoted by a Polycomb Group (PcG)->Home… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 78 publications
0
30
0
Order By: Relevance
“…and A10 [4,14,34,35]. Subsequently these NBs enter quiescence and start dividing again in early larval stages ( Fig 1A).…”
Section: Plos Geneticsmentioning
confidence: 90%
See 3 more Smart Citations
“…and A10 [4,14,34,35]. Subsequently these NBs enter quiescence and start dividing again in early larval stages ( Fig 1A).…”
Section: Plos Geneticsmentioning
confidence: 90%
“…This is mainly contributed by a gradient of NB proliferation as well as a switch in cell division mode (from Type I>0) along the AP axis (regulated by Hox genes). These molecular events together reduce the number of cells in these segments and lay the foundation of a wedge shaped CNS tapering towards the terminal region later in development [34,35].…”
Section: Role Of Nb Proliferation Division Mode and Apoptosis In Patmentioning
confidence: 99%
See 2 more Smart Citations
“…As anticipated from previous studies, we observed a reduction in NB numbers in both SoxN and wor mutants ( Figure 3A-C, 3F). The UAS-Quad and -Quad D combinatorial expression, which includes SoxN or wor, can trigger massive ectopic NB generation in the embryonic ectoderm or wing imaginal discs ( Figure 1E-G) (Bahrampour et al, 2017;Bahrampour et al, 2019). However, we did not previously test the effects of single SoxN or wor misexpression from an early Gal4 driver.…”
Section: Soxn and Wor Regulate The Notch Pathwaymentioning
confidence: 99%